1988
DOI: 10.1080/01490408809512191
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of consumer loyalty to municipal recreation programs

Abstract: This study of participant loyalty to selected municipal recreation programs emerged from the consumer behavior literature on brand loyalty, applying the concept to a service-oriented leisure agency. Using a two-dimensional measure of loyalty, incorporating both a behavioral or repeat purchasing dimension and an attitudinal or commitment dimension, this study found that participants exhibited a high degree of repeat purchasing and only a moderate level of commitment to agency programs. Loyalty segmentation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 10 publications
1
36
0
1
Order By: Relevance
“…This research uses more elaborate conceptualisations of both proportion of purchase of a specific brand together with an (affective) attitude measure using a single scale 40 or multiscale items. 41 In addition to these dimensions, later authors included what has been termed cognitive loyalty. 42,43 Cognitive loyalty involves the consumers rationally and consciously evaluating information about the benefits of competing offerings before a purchase is effected.…”
Section: Switching Cost and Customer Loyaltymentioning
confidence: 99%
“…This research uses more elaborate conceptualisations of both proportion of purchase of a specific brand together with an (affective) attitude measure using a single scale 40 or multiscale items. 41 In addition to these dimensions, later authors included what has been termed cognitive loyalty. 42,43 Cognitive loyalty involves the consumers rationally and consciously evaluating information about the benefits of competing offerings before a purchase is effected.…”
Section: Switching Cost and Customer Loyaltymentioning
confidence: 99%
“…Baloglu (2001), Pritchard and Howard (1997), and Rowley and Dawes (2000) have utilised cluster analysis of behavioural consistency and psy- chological attachment items to confirm the four quadrant structures proposed by Selin et al (1988) and Backman (1988). These studies have confirmed that four distinct types of loyalty exist in a multitude of settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As suggested by Backman (1991) 'spuriously loyal' visitors probably continue to purchase even though they are not attached because they feel the cruise line is their best or only option. According to Selin et al (1988) since spuriously loyal consumers lack a true attachment to a product, they may quickly switch their patronage to another provider offering a more convenient or less expensive product.…”
Section: Loyalty Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…As an attitude and emotion, pleasure strongly affects post-purchase factors. In online shopping, Chiu et al's research [42], among many other similar studies [24,25,46,47,108,217,221], showed that perceived ease of use, perceived usefulness, and enjoyment are significant positive predictors of customers' repurchase intentions. Thus, pleasure can conceivably be thought of as an antecedent of loyalty.…”
Section: During-purchase Factorsmentioning
confidence: 99%